2012
DOI: 10.1186/1471-2458-12-426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of the output-based aid voucher program to increase uptake of gender-based violence recovery services in Kenya: A qualitative evaluation

Abstract: BackgroundFew studies in Africa have explored in detail the ability of output-based aid (OBA) voucher programs to increase access to gender-based violence recovery (GBVR) services.MethodsA qualitative study was conducted in 2010 and involved: (i) in-depth interviews (IDIs) with health managers, service providers, voucher management agency (VMA) managers and (ii) focus group discussions (FGDs) with voucher users, voucher non-users, voucher distributors and opinion leaders drawn from five program sites in Kenya.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Victims of IPV were offered support in the form of reproductive health vouchers available at healthcare facilities, giving them access to medical services (including HIV care), psychological care, and social services. Results showed that there were many barriers to the uptake of these services (Njuki et al, 2012), mostly centred around a lack of general awareness by healthcare employees and patients regarding the vouchers and benefits, and also poor response from law enforcement services.…”
Section: Intervening In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Victims of IPV were offered support in the form of reproductive health vouchers available at healthcare facilities, giving them access to medical services (including HIV care), psychological care, and social services. Results showed that there were many barriers to the uptake of these services (Njuki et al, 2012), mostly centred around a lack of general awareness by healthcare employees and patients regarding the vouchers and benefits, and also poor response from law enforcement services.…”
Section: Intervening In Sub-saharan Africamentioning
confidence: 99%
“…Multivariable logistic regression analyses suggested that inequitable attitudes and couple discordance were associated with higher risk of IPV. Njuki et al (2012) Kenya, women and men n ¼ 97 interviews 27 focus groups…”
Section: Intervening In Sub-saharan Africamentioning
confidence: 99%
“…The larger study used a pretest and posttest design with a comparison group. Preintervention (pre‐FMS policy) data were from a 2012 study that evaluated the effect of the reproductive health vouchers program in Kenya on health outcomes by comparing communities in voucher and comparable nonvoucher sites . The postintervention data were collected in the same communities included in the 2012 study and involved both quantitative and qualitative components.…”
Section: Methodsologymentioning
confidence: 99%
“…Following the pilot, the program was expanded to one additional county (Kilifi) as well as to additional facilities in the pilot counties, and implementation continued until late 2016. The results of this initiative indicated promising opportunities for improving access, coverage, and quality for targeted low‐income beneficiaries …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation